ANALISIS PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK TERHADAP KEPUASAN DAN LOYALITAS NASABAH BANK SYARIAH INDONESIA DI KOTA SEMARANG - Fatima, Syamsyiar Ika (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2023)
The increasing presence of the Islamic banking industry in Indonesia has created competition in retaining and acquiring customers. Bank Syariah Indonesia in Semarang City must pay attention to service quality and product quality in order to achieve customer satisfaction and increase the loyalty of its customers. This study aims to determine the effect of service quality, product quality on customer satisfaction and loyalty of Bank Syariah Indonesia Semarang City.This study used multiple linear regression analysis techniques with data testing using the SPSS Statistics 25 program. The population in this study were customers of Bank Syairah Indonesia, Semarang City. The required sample is 100 people with a purposive sampling method and data collection in this study is through an online questionnaire.The results of this study indicate that partially model I service quality and product quality have a positive and significant effect on customer satisfaction. The R Square value is 0.677, this means that the ability of service quality and product quality variables to explain customer satisfaction is 67.7 precent while the remaining 32,3 precent is explained by other factors outside in this study. Model II partially shows that service quality, product quality and customer satisfaction have a positive and significant effect on customer loyalty. The R Square value is 0.696, this means that the ability of the variables of service quality, product quality and customer satisfaction to explain customer loyalty is 69.6 precent while the remaining 30.4 precent is explained by other factors outside in this study.Keywords: service quality, product quality, customer satisfaction, customer loyalty.